Analisis Perbandingan Brand Equity Produk Obat Anti Nyamuk Oles Merek Autan Dengan Merek Soffel Di Kota Denpasar - Armandhani, Herdian; Sukaatmadja, I Putu Gde (E-Jurnal Manajemen; Vol 3 No 1 (2014), 2014)
This study aims to determine differences in brand equity as well as as its elements (brand awarenss, brand associations, brand perceived quality, and brand loyalty) between repellent product with brand Autan and Soffel. The data analysis technique used is different analysis technique t-test with paired samples. Based on this research, the research  that there is a difference between brand equity Autan with Soffel. Soffel brand equity is higher than Soffel. As a suggestion for the  Autan producer it is suggested to increase its product brand equity, especially in the value of brand associations, while suggestion for Soffel producer it is suggested pursuing a strategy to maintain and enchance its product brand equity value in order to give a significant difference with the brand equity of Autan repellent.   Keywords  : brand equity, brand awareness, brand association, brand perceived quality, and brand loyalty.